The Role of Actor Networks in Public Policy Formulation - Rizky Ilhami; Willya Achmad (International Publisher, 2023)
This research discusses the role played by actor networks in the process of formulating public policy. With the increasing complexity in the public policy environment, the role of actor networks becomes crucial in influencing and shaping the resulting policy direction. This research uses a qualitative approach by collecting data through in-depth interviews and documentary analysis. Based on the research results, it can be concluded that actor networks play a crucial role in the process of formulating public policy. These roles include the roles of subjects with high importance but low power, key players with high interest and power, other followers who represent group voices that may be less heard, and supporters who have power but low interest. However, the process of formulating public policy is faced with a number of challenges, including the complexity of organizational structures, conflicts of interest between actors, lack of resources, and resistance to change. To overcome these challenges, close collaboration between all parties involved, open communication, and wise management of differences and conflicts that arise is required. Through these efforts, the policy formulation process can become more inclusive, responsive and effective in meeting the needs of society as a whole.